Variation in the management of ductal carcinoma in situ in the UK: Results of the Mammary Fold National Practice Survey. Issue 8 (August 2016) - ,; Ashken, L.; Ives, C.; Kim, B.; Potter, S.; Rattay, T.; Remoundos, D.; Zeidan, B.; Williams, K.; Bathla, S.; Fatayer, H.; Sirianni, C.; et al.
Abstract: Introduction: Ductal carcinoma in situ (DCIS) accounts for approximately 10% of all newly-diagnosed breast cancers in the UK. The latest national guidelines were published in 2009 and may not reflect current best practice. We aimed to explore variation in the current management of DCIS to support the need for updated guidelines. Methods: A national practice questionnaire was developed by the Mammary Fold Academic Committee (MFAC) focussing on the pre, intra and post-operative management of DCIS. Trainees at UK breast units were invited to complete the questionnaire at their multidisciplinary team meeting to provide a comprehensive picture of current national practice. Results: 76 of 144 UK breast units (52.8%) participated in the survey. Variation was observed in radiological pre-operative assessment with only 33/76 units (43.4%) performing routine ultrasound assessment of the tumour or axilla. There was no clear consensus regarding indications for mastectomy; multifocality (38.2%) and extensive microcalcifications (34.2%) were the most frequent indications. 34/76 units (44.7%) offered nipple sparing mastectomy. 33/76 units (43.3%) perform sentinel node biopsy in the presence of a palpable/mass lesion and 51/76 (67.1%) at the time of mastectomy. The most widely accepted pathological radial margin remained 2 mm (36.8%). The commonest factors in decision-making for radiotherapy were tumour grade (51.3%) and size (35.5%). Only 12 units (15.8%) routinely used the Van Nuys Prognostic Index. Approximately half of all breast units offer clinical long-term follow-up. Discussion: There is marked variation in the management of DCIS in the UK. Updated evidence-based guidelines may standardise practice and improve outcomes for patients.